2012
DOI: 10.1108/20441281211198835
|View full text |Cite
|
Sign up to set email alerts
|

Improving health and lives: The Learning Disabilities Public Health Observatory

Abstract: Purpose -The purpose of this paper is to describe the first 15 months of operation of an innovative specialist national public health observatory for intellectual disability.Design/methodology/approach -The paper provides a narrative account of aims and achievements of the service.Findings -In the first 15 months of operation the observatory has: made available to those involved in commissioning health and social care services, a wealth of information on the health needs of people with intellectual disabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 8 publications
2
79
0
1
Order By: Relevance
“…Maes et al (2003) and Emerson et al (2010), found similar results in caregivers of child and adult with an ID-MD. The presence of behavioral problems, psychotic and affective symptoms increases the risk of having greater family burden.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Maes et al (2003) and Emerson et al (2010), found similar results in caregivers of child and adult with an ID-MD. The presence of behavioral problems, psychotic and affective symptoms increases the risk of having greater family burden.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, a holistic view should include the understanding of family burden in biopsychosocial framework (World Health Organization [WHO], 2001). One study of unpaid caregivers of people with learning disabilities referring to intellectual disabilities in the United Kingdom found that 75% of caregivers of an adult with ID had been caring for more than 20 years, 26% reported not being in paid employment due to their responsibilities, and 48% spent 100 or more hours a week caring for that person (Emerson et al, 2010). However, 90% of those caregivers felt they were or were usually involved as much as they wanted to be in decisions about the care and treatment of the person they cared for.…”
mentioning
confidence: 99%
“…164 Knowledge of the health risks associated with specific syndromes is of value in targeting the content of health checks;…”
Section: Secondary Health Carementioning
confidence: 99%
“…39,50 This may be because the majority of these patients do not use specialised services for adults with ID and, as a result, are not well known to primary care. The prevalence estimate of 2.17% calculated by Public Health England in 2013 50 would mean that three out of four patients with ID are not currently on QOF learning disability registers.…”
Section: Quality and Outcomes Framework And Learning Disabilitymentioning
confidence: 99%
“…An associated reduction in emergency hospital admissions is likely to be a key measurable and valued benefit from annual health checks, as people with ID experience high levels of emergency admissions. 39 Additionally, unplanned Determine whether or not practice participation in the annual health check DES improves outcomes for people with ID See Chapter 6…”
Section: Evidence Base For Annual Health Checksmentioning
confidence: 99%